A comparative evaluation of propolis and light-cured ormocer-based desensitizer in reducing dentin hypersensitivity - Snigdha Maity; Vidya Priyadharshini; Suman Basavaraju (Wolters Kluwer Medknow Publications, 2020)
Objectives: The purpose of the study was to evaluate and compare the clinical efficacy and the durability of propolis and Light-cured ormocer-based desensitizer (Admira Protect, Voco: Cuxhaven Germany) in the treatment of dentin hypersensitivity (DH). Materials and Methods: The study was conducted over a period of 2 months on 13 patients with 72 hypersensitive teeth, randomly allocated into three treatment groups: Group A: Treated with Propolis, Group B: Admira protect (Voco: Cuxhaven Germany), and Group C: Sterile water (Placebo control). Baseline sensitivity was recorded by the operator using tactile and evaporative stimuli. Visual analog scale (VAS) was used to record the degree of sensitivity perceived by the patients. All the groups received applications of allotted materials on day 1, 7, 14, and 21. After each applications VAS scoring was recorded. On day 30 and 60, only pain evaluation was done to determine the durability of each test materials. Statistical Analysis: One-way ANOVA, repeated measure ANOVA and post hoc test was done for multiple comparison. Results: All the groups showed significant results in reducing DH. Among Groups A and B, Group B showed immediate postoperative result at the end of the 1st week. Conclusion: Both the test materials were effective in reducing DH but Admira protect was found to be more efficient in reducing pain with longer duration of action (CTRI regd no: CTRI/2017/12/010755).